Promoting MSME Sustainability: The Role of Halal Certification and E-Commerce - Riska Amalia; Levina Rachmawati Putri; Maulina Agustin (Talenta Publisher, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play a strategic role in the Indonesian economy, but still face various challenges in achieving business sustainability. Two factors considered capable of driving MSME sustainability are halal certification and the use of e-commerce. Halal certification serves as a guarantee of quality and consumer trust, while e-commerce opens wider market access and increases business efficiency. This study aims to comprehensively examine the role of halal certification and e-commerce in driving MSME sustainability through a literature study approach. The research method used is descriptive qualitative with content analysis of various relevant scientific sources. The results of the study indicate that halal certification and e-commerce, individually and simultaneously, contribute positively to increasing the competitiveness, performance, and sustainability of MSMEs. The synergy between the two is an important strategy in facing the challenges of the digital economy and global competition.